High hepatic exposure of furanocoumarins in Radix Angelica dahuricae is associated with transporter mediated active uptake. (15th February 2018) - Chen, Lin; Yang, Haiying; Yu, Chenchen; Yuan, Mei; Li, Hua
Abstract: Ethnopharmacological relevance: Radix Angelica dahuricae ( RAD ), the roots of Angelica dahurica (Hoffm.) Benth. & Hook.f. ex Franch. & Sav, is a well-known traditional Chinese medicine (TCM) and has been used for centuries to treat headaches, toothaches, nose congestion, abscesses, furunculoses, and acne. This herb is also one of frequently reported TCMs showing the herb-drug interaction potential. Furanocoumarins are main bioactive components of RAD . Aim of the study: This study is designed to characterize the tissue distribution profiles of furanocoumarins after oral administration of RAD extract in rats and to explore the mechanism underlying the high hepatic exposure of the major furanocoumarins. Materials and methods: The tissue distribution of nine furanocoumarins was determined in rats after an oral dose of 0.46 g/kg RAD extract using high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Unbound fractions (ƒu ) of major furanocoumarins, including imperatorin (IM), isoimperatorin (IIM), bergapten (BER) and oxypeucedanin hydrate (OXYH), were measured in rat plasma and selected tissue homogenates (liver, kidney, lung and brain) with Rapid Equilibrium Dialysis (RED) method. The temperature dependent hepatic uptake of IM, IIM, BER and OXYH were evaluated in suspended rat primary hepatocytes at 4 °C or 37 °C by the oil-spin method. The uptake kinetics was conducted in the cells over a wide concentration range. The furanocoumarins were co-incubated with a panel of transporter inhibitors to investigate the involvement of uptake transporters in the hepatic uptake. The transcellular transport characteristics of IM, IIM, BER and OXYH were further assessed using Caco-2 cell monolayer model. Results: IM, IIM, BER and OXYH were found to be the major bioactive furanocoumarins in rat plasma and tissues, representing more than 90% exposure for all the detected furanocoumarins. The most concentrative organ of major furanocoumarins was the liver, with liver-to-plasma exposure ratio ( K p, AUC ) of 5.1, 6.5 and 4.7 for IM, IIM and BER, and 2.3 for OXYH, respectively. IM, IIM and BER also showed higher concentrations in the kidney with K p above 2.2. The higher protein binding of the furanocoumarins partially contributed to their higher tissue exposure. In suspended rat primary hepatocyte, the hepatic uptake of IM, IIM, BER and OXYH was temperature-dependent, with considerably higher uptake at 37 °C than at 4 °C. Uptake kinetics indicated that the hepatic uptake of IM, IIM, BER and OXYH involved both active transport and passive diffusion processes. For IM, IIM and BER, the contribution of the active transport was greater than the passive process, with the CLactive /CLuptake > 72%. Ritonavir (RTN) and cyclosporine A (CsA), the known inhibitors of organic anion transporting polypeptide (Oatp) significantly inhibited the hepatic uptake of IM and BER, while the inhibitor of the organic anion transporters (Oat) probenecid (PBC) remarkably reduced IIM uptake. In the Caco-2 cell model, the furanocoumarins were highly permeable in the apical to basolateral direction without notable active efflux. Conclusion: The furanocoumarins rapidly and widely distributed into various tissues after oral dose of the RAD extract. IM, IIM, BER and OXYH were the major components detected in both plasma and tissues. Liver was the most distributed tissue of the total and free furanocoumarins. Non-specific protein binding contributed partially to the higher tissue exposures of these bioactive components. The Oatp and Oat mediated active uptake played the primal role in the high hepatic exposure of the furanocoumarins. Graphical abstract: